Assessment of modified Zancolli arthroplasty for basal thumb arthritis - Bahaa A Kornah; Maysra A.E Bayuomy; Ahmed G Ibrahim (Wolters Kluwer Medknow Publications, 2021)
Background and aim The trapeziometacarpal arthritis is one of the most common joint problems affecting women after the age of 50 years. Surgery is indicated after failure of conservative treatment with continuation of pain and functional disabilities. One of the most reported and well-known surgical procedure for management of basal thumb arthritis is the ligament reconstruction and tendon interposition arthroplasty. The aim of the study was to evaluate patients who underwent modified Zancolli arthroplasty for basal thumb arthritis. Patients and methods The study included 15 patients with basal thumb arthritis (three males and 12 females). Full clinical examination and scoring of the hand was done using Quick DASH, visual analog scale, measuring range of motion, and grip strength. All patients underwent full radiological and laboratory investigations. Results Overall pain intensity was measured with a visual analog scale, which ranged from 5-10 preoperatively and ranged from 0 to 1 6 months postoperatively. Regarding the DASH score, there was improvement from a mean of 64.48±16.61 points preoperatively to a mean of 1.37±1.67 points postoperatively. The mean postoperative abduction was 75% to the normal side, opposition was 80% to the normal side, and power grip was 90% to the normal hand. Conclusion Modified Zancolli arthroplasty is an effective means of treating symptomatic patients with trapeziometacarpal arthritis who failed to improve with nonsurgical measures. This technique ensures a dynamic fixation of the apical ligament and provides better stability. The procedure is simple both technically and regarding postoperative care.